Hubungan Terpaan Kampanye Food Waste dan Sikap terhadap Perilaku Mengurangi Pembuangan Makanan dengan Minat Mengurangi Pembuangan Makanan - Annisa Ilmi, Rizky; Setyabudi, Djoko (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
The purpose of this study was to determine the correlation of food waste campaign exposure and attitude toward reduce wasting food behavior with interest to reduce wasting food. The theory used in this study is motivation protection theory and theory of planned behavior. The sample technique used is Non-Probability Sampling, namely Purposive Sampling. The number of samples discussed in this study were 60 respondents with college student characters domiciled in Semarang City aged 18-24 years old who have heard, read, or listened to campaign about food waste.Analysis of the data used in this study is the Kendall’s Tau B correlation test. The results of the study show that the food waste campaign exposure (X1) with the interest to reduce wasting food (Y) doesn’t have significant relationship where the significant values generated after testing with Kendall’s Tau B correlation with SPSS are ammounted to 0,084. The second hypothesis shows that there is a significant relationship between attitude toward reduce wasting food behavior (X2) with interest to reduce wasting food (Y) where the significant values generated after testing with Kendall’s Tau B correlation with SPSS are ammounted to 0,000 and have strong correlation coefficient where values was 0,540.